Adaptive sports activities for the adolescents with mild intellectual disabilities in China - Sun, Shenglin (Journal of Education for Sustainability and Diversity, 2025)
This article delves into the integration of adolescents with mild intellectual disabilities into mainstream sport classes within China's special education framework. As the practice evolves, an increasing number of children with special needs are being included in regular educational settings, emphasizing a shift from mere inclusion to the pursuit of enhanced educational quality. Physical education is pivotal for the development of these students, aiming to elevate the caliber of inclusive education. However, the current sports development for students with special needs is fraught with issues, including neglect and marginalization in inclusive environments and a lack of adequate resources and personalized plans, which exacerbates the disparity between them and their peers. This disparity not only impedes their full integration into general physical education but also adversely affects their physical and mental well-being and the overall quality of inclusive education. The study underscores the imperative to refine sport teaching methodologies and to devise tailored training programs to bolster the competencies of students with special needs, thereby boosting their engagement in sports and fostering their inclusion in standard sport settings. Through a systematic literature review and mathematical statistics, the study evaluates the status quo of integrated physical education in China, pinpointing the prevalent conditions, challenges, and areas for improvement. The findings reveal that the integration of children with mild intellectual disabilities into standard physical education classes is subpar, primarily constrained by scarce resources, professional development gaps among educators, a dearth of practical experience, and the inherent challenges encountered by the students themselves.